The genomic history and global migration of a windborne pest - Hu, Qing-Ling; Zhuo, Ji-Chong; Fang, Gang-Qi; Lu, Jia-Bao; Ye, Yu-Xuan; Li, Dan-Ting; Lou, Yi-Han; Zhang, Xiao-Ya; Chen, Xuan; Wang, Si-Liang; Wang, Zhe-Chao; Zhang, Yi-Xiang; et al. (American Association for the Advancement of Science, 2024)
Many insect pests, including the brown planthopper (BPH), undergo windborne migration that is challenging to observe and track. It remains controversial about their migration patterns and largely unknown regarding the underlying genetic basis. By analyzing 360 whole genomes from around the globe, we clarify the genetic sources of worldwide BPHs and illuminate a landscape of BPH migration showing that East Asian populations perform closed-circuit journeys between Indochina and the Far East, while populations of Malay Archipelago and South Asia undergo one-way migration to Indochina. We further find round-trip migration accelerates population differentiation, with highly diverged regions enriching in a gene desert chromosome that is simultaneously the speciation hotspot between BPH and related species. This study not only shows the power of applying genomic approaches to demystify the migration in windborne migrants but also enhances our understanding of how seasonal movements affect speciation and evolution in insects.